Alfalfa hay and wet corn gluten feed levels in steam-flaked corn finishing diets - J.J. Sindt; J.N. Pike; Sean P. Montgomery; C.M. Coetzer; T.B. Farran; T.J. Kessen; R.T. Ethington; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2001)
A 153-day finishing experiment was conducted using 631 heifers to determine optimum alfalfa hay and wet corn gluten feed (WCGF) combinations in steam-flaked, corn-based diets. Diets contained either 2 or 6% alfalfa hay and 25, 35, or 45% WCGF (dry basis). Performance was similar (P>0.16) for cattle fed 2 or 6% alfalfa hay. Gain efficiencies (P<0.05) and fat thickness (P<0.10) declined linearly with increasing amounts of WCGF. For heifers fed 2% alfalfa hay, ribeye area increased with increasing dietary WCGF. However for heifers fed 6% alfalfa hay, ribeye area decreased with increasing dietary WCGF. Liver abscesses were lowest for heifers fed 35% WCGF. Alfalfa hay fed at 2% of diet dry matter is sufficient for steam-flaked corn diets containing 25, 35 or 45% WCGF.
Keywords: Cattlemen& #x27; s Day; 2001; Kansas Agricultural Experiment Station contribution; no. 01-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 873; Beef; Wet corn gluten feed; Steam-flaked corn; Finishing cattle